2019
DOI: 10.30969/acsa.v15i4.1124
|View full text |Cite
|
Sign up to set email alerts
|

Características agronômicas de rabanete submetido a diferentes substratos preparados com coprólitos de minhoca

Abstract: O objetivo deste trabalho foi avaliar a produção de rabanetes cultivados em substratos preparados a partir da mistura de coprólitos de minhocas Chibui bari, solo e substrato commercial (SC). O experimento foi realizado em casa de vegetação na Universidade Federal do Acre, utilizando-se delineamento inteiramente casualizado com sete tratamentos e seis repetições. Os substratos foram assim formulados: T1 (100% SC); T2 (50% SC + 50% Solo); T3 (100% Solo); T4 (100% Coprólito); T5 (75% Coprólito + 25% Solo); T6 (50… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 6 publications
0
1
0
Order By: Relevance
“…-y (T 1 ) = -0. With the objective of evaluating the influence of phosphorus fertilization on radish cultivation under controlled conditions, Melo et al (2021) found that treatments containing nitrogen, potassium and twice the recommended phosphorus were the ones with the greatest number of leaves, the greatest root diameter and length, and also the highest chlorophyll content. However, when the dose of phosphorus is quadrupled there is a reduction of 9.5% and when it is increased eight times this reduction is 15.5%, indicating the effect of increased fertilization on the photosynthetic rate.…”
Section: Resultsmentioning
confidence: 99%
“…-y (T 1 ) = -0. With the objective of evaluating the influence of phosphorus fertilization on radish cultivation under controlled conditions, Melo et al (2021) found that treatments containing nitrogen, potassium and twice the recommended phosphorus were the ones with the greatest number of leaves, the greatest root diameter and length, and also the highest chlorophyll content. However, when the dose of phosphorus is quadrupled there is a reduction of 9.5% and when it is increased eight times this reduction is 15.5%, indicating the effect of increased fertilization on the photosynthetic rate.…”
Section: Resultsmentioning
confidence: 99%